Sesana Guru Nabe Dalam Upacara Padiksaan Di Desa Pergung Kecamatan Mendoyo Kabupaten Jembrana Kajian Pendidikan Agama Hindu - I Komang Sukanada (Jayapangus Press, 2018)
Religion has philosophical, ethical and moral values which are used as references in social life. In this case the Ceremony is one form of manifestation in increasing sraddha and devotional service for Hindus before Ida Hyang Widhi Wasa. The same goes for the implementation of Yajña in Pergung Village, Mendoyo District, Jembrana Regency which was implemented through the Rsi Yajña ceremony, which was the implementation of the Examination Ceremony. Considering the importance of Sesana Guru Nabe in the Padiksa Ceremony which not only gave birth to Pandita in a narrow sense, but was able to give birth to Pandita who could maintain balance in the community, especially the Pergung Village.